The Implementation Of Network Management And Security Using Mikrotik And Proxy Server At SMK N 3 Seluma - Indra Saputra; Toibah umi Kalsum; Hendri Alamsyah (Fakultas Ilmu Komputer Universitas Dehasen Bengkulu, 2024)
The aim of this research is to carry out computer network management and security at SMK Negeri 3 Seluma by using a proxy device and a sequid proxy server as an external proxy server. The research method used in this research is PPDIO method consisting of Prepare, Plan, Design, Implement, Operate and Optimize. The hardware used to configure network management is Mikrotik Roadboard, while the software used to configure network management and security is Winbox and Squid proxy server. The results of research on the implementation of network management were the formation of a network using a proxy configuration at SMKN 3 Seluma. toward network security, filtering of social media websites and websites suspected of containing viruses can be carried out according to the design and the blocking is successful.